DIGITIZATION IS NOT ONLY MAKING IMAGES: MANUSCRIPT STUDIES AND DIGITAL PROCESSING OF MANUSCRIPTS - UHLÍŘ, ZDENĚK (Knygotyra, 2015)
Author deals with the link between the digital processing of historical documents, especially manuscripts and the manuscript studies, codicology and bibliology and cultural history as well. The greatest part of the paper applies to the case study about the Manuscriptorium digital library which is provided by the National Library of the Czech Republic.